Treatment of Insertional Achilles Tendinopathy with MRI Confirmed Small or No Tear Using a Gastrocnemius Recession. Issue 4 (16th October 2019) - Long, Joseph M; Whitehead, Brent; Zehnder, David; Large, Bryan; Cheney, Nicholas; Law, Timothy
Category: Ankle Introduction/Purpose: Insertional Achilles tendinopathy can be a distressing problem for an active patient. Treatment begins conservatively, and when this fails a patient's next best option may involve operating on the affected tendon. Depending on the disease state of the tendon, the surgeon may decide to repair or augment the Achilles with a flexor hallucis longus (FHL) transfer. The current literature supports the gastrocnemius recession for non-insertional cases, but is inconsistent in its efficacy for insertional cases. Our study looks at how patients with insertional Achilles tendinopathy with a small tear involving 20% of the tendon or less responded to an isolated gastrocnemius recession. Our hypothesis was that patients could do well without the need for a large repair or FHL transfer procedure. Methods: We retrospectively reviewed patients who underwent an isolated gastrocnemius recession for recalcitrant insertional Achilles tendinopathy between January 2015 and July 2018. Patients were included based on the diagnosis of insertional Achilles tendinopathy, having an MRI confirming tendinopathy, a tear involving less than 20% of the tendon or no tear, and no other concurrent pathologies. These criteria yielded 14 patients. One of these 14 patients was removed from the data analysis due to non-surgical complaints after surgery stemming from new onset posterior ankle pain. The patient charts were reviewed for their subjective VAS pain scores during office visits pre and postoperatively. Immediate preoperative visit, initial postoperative visit and final visit VAS scores were recorded. Results: The average time of chart follow up for the 13 patients included in the study was 15.5±10.5 weeks postoperatively (range 4-38). 2 patients were found to have a tear <20% (15%), and the remaining 11 patients were found to have no tear on their MRI (85%). The average final preoperative VAS pain score for the patients was 5.4±1.8 (range 3-9). The average final postoperative VAS pain score for the patients was 0.9±1.3 (range 0-5). These values were found to be statistically different (p<0.001). Of note all patients saw a reduction in their pain score of at least 2 points. Conclusion: Previous literature is inconclusive on the efficacy of the gastrocnemius recession for insertional Achilles tendinopathy. No other study has identified the amount or type of tendon involvement by advanced imaging. Our study supports the notion that patients with MRI confirmed tendinopathy and a tear involving less than 20% of the tendon or no tear, often do quite well in reaching a reduction in their pain. Our study is limited in power due to our small sample size, but the results suggest that this procedure deserves more attention for the treatment of insertional Achilles tendinopathy when appropriate.